Deposit Insurance, Regulatory Forbearance and Economic Growth: Implications for the Japanese Banking Crisis - Robert Dekle; Kenneth Kletzer (Center for Economic Studies and ifo Institute (CESifo), 2004)
An endogenous growth model with financial intermediation is used to show how public deposit insurance and weak prudential regulation can lead to banking crises and permanent declines in economic growth. The impact of regulatory forbearance on investment, saving and asset price dynamics under perfect foresight are derived in the model. The assumptions of the theoretical model are based on essential features of the Japanese financial system and its regulation. The model demonstrates how banking and growth crises can evolve under perfect foresight. The dynamics for economic aggregates and asset prices predicted by the model are shown to be generally consistent with the experience of the Japanese economy and financial system through the 1990s. We also test our maintained hypothesis of rational expectations using asset price data for Japan over the 1980s and 1990s. An implication of our analysis is that delaying the resolution of banking crises adversely affects future economic growth.
Keywords: 330